Pengaruh Social media marketing, Brand Image, Dan Brand Trust Terhadap Keputusan Pembelian Skincare Camille Beauty (Studi Pada Followers Media Sosial Camille Beauty) - Safira, Monica Novita; Malikah, Anik; Athia, Ita (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of social media marketing, brand image, and brand trust on the purchasing decisions of Camille Beauty skincare products among its social media followers. This study used a quantitative method with an explanatory research approach. The sample in this study was 75 respondents from Camille Beauty's Instagram and TikTok followers. Data collection used a questionnaire, data analysis using multiple linear regression using SPSS 25 software. The results of this study explain that Social media marketing, Brand Image, and Brand trust have a significant positive influence on purchasing decisions. This study emphasizes the importance of digital marketing strategies, strengthening brand image, and building consumer trust to improve purchasing decisions among social media users Keywords : Social Media Marketing, Brand Image, Brand Trust, Purchasing Decisions